2017
DOI: 10.1128/aem.01590-17
|View full text |Cite
|
Sign up to set email alerts
|

In Bacillus subtilis, the SatA (Formerly YyaR) Acetyltransferase Detoxifies Streptothricin via Lysine Acetylation

Abstract: Soil is a complex niche, where survival of microorganisms is at risk due to the presence of antimicrobial agents. Many microbes chemically modify cytotoxic compounds to block their deleterious effects. Streptothricin is a broad-spectrum antibiotic produced by streptomycetes that affects Gram-positive and Gram-negative bacteria alike. Here we identify the SatA (for treptothricinceyltransferase , formerly YyaR) enzyme of as the mechanism used by this soil bacterium to detoxify streptothricin. strains lacking wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 42 publications
1
25
0
2
Order By: Relevance
“…The oligomeric state of all the purified BsSatA variants was determined by size exclusion chromatography using fast protein liquid chromatography (FPLC). Previously, we showed that BsSatA WT forms dimers in solution (26). The retention time of all B. subtilis BsSatA variants was consistent with a dimeric state ( Table 1), suggesting that the impaired ability to confer streptothricin resistance in S. enterica by the BsSatA variants was not due to a block in dimerization.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…The oligomeric state of all the purified BsSatA variants was determined by size exclusion chromatography using fast protein liquid chromatography (FPLC). Previously, we showed that BsSatA WT forms dimers in solution (26). The retention time of all B. subtilis BsSatA variants was consistent with a dimeric state ( Table 1), suggesting that the impaired ability to confer streptothricin resistance in S. enterica by the BsSatA variants was not due to a block in dimerization.…”
Section: Resultssupporting
confidence: 60%
“…These results suggested that the residues L128 and A137 play a role in protein folding, oligomerization, substrate binding, or catalysis. In previous studies, we showed that S. enterica strains that synthesize BsSatA WT are resistant to 10 M streptothricin without the addition of inducer (26), indicating that the P BAD promoter of pCV1 allows for enough residual expression of satA in the absence of arabinose to confer resistance. Importantly, adding arabinose to the medium (200 M) did not overcome the inhibitory effect of streptothricin when the tester strain synthesized either the BsSatA L128F or BsSatA A137T variant ( Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The clarified cell‐free extract was loaded onto a 5‐mL Ni‐NTA affinity column (HisPur; ThermoFisher Scientific) and purified as described (Burckhardt and Escalante‐Semerena, ). Briefly, the column was washed with 10 bed volumes of binding buffer followed by six bed volumes of wash buffer [HEPES (50mM, pH 7.5) + NaCl (500 mM) + imidazole (40 mM)].…”
Section: Methodsmentioning
confidence: 99%
“…Many of these acetyltransferases belong to the GCN5‐related N ‐acetyltransferase (GNAT) protein superfamily (PF00583), all sharing a core catalytic domain despite low sequence homology (Vetting et al , ). GNATs are found in all domains of life and transfer an acetyl group from acetyl‐coenzyme A (AcCoA) to amines of small molecules or the amino group ( Nα ) of the N terminus of proteins, or Nε of lysyl residues in proteins or small molecules (Tucker and Escalante‐Semerena, ; Burckhardt and Escalante‐Semerena, ). Acetylation of proteins can impact their stability, structure or activity (Walsh et al , ).…”
Section: Introductionmentioning
confidence: 99%